2006
DOI: 10.1128/aem.00228-06
|View full text |Cite
|
Sign up to set email alerts
|

Okadaic Acid, an Apoptogenic Toxin for Symbiotic/Parasitic Annelids in the Demosponge Suberites domuncula

Abstract: The role of okadaic acid (OA) in the defense system of the marine demosponge Suberites domuncula against symbiotic/parasitic annelids was examined. Bacteria within the mesohyl produced okadaic acid at concentrations between 32 ng/g and 58 ng/g of tissue (wet weight). By immunocytochemical methods and by use of antibodies against OA, we showed that the toxin was intracellularly stored in vesicles. Western blotting experiments demonstrated that OA also existed bound to a protein with a molecular weight of 35,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…This is indeed the case of the marine sponge Suberites domuncula harboring bacteria containing OA. Here, low OA concentrations (<100 nM) stimulate the defense system against bacteria [65], whereas high OA concentrations (>500 nM) induce apoptosis in symbiotic or parasitic annelids [65,66] while preventing self-intoxication in the sponge [67,68]. Furthermore, another type of defensive role for OA has been reported in the sponge Lubomirskia baicalensis , where OA seems to facilitate the expression of the heat shock protein hsp70 during the winter season, helping this species withstand water temperatures of 0 °C below the sea ice [69].…”
Section: Response Strategies To Okadaic Acid In Marine Invertebratesmentioning
confidence: 99%
“…This is indeed the case of the marine sponge Suberites domuncula harboring bacteria containing OA. Here, low OA concentrations (<100 nM) stimulate the defense system against bacteria [65], whereas high OA concentrations (>500 nM) induce apoptosis in symbiotic or parasitic annelids [65,66] while preventing self-intoxication in the sponge [67,68]. Furthermore, another type of defensive role for OA has been reported in the sponge Lubomirskia baicalensis , where OA seems to facilitate the expression of the heat shock protein hsp70 during the winter season, helping this species withstand water temperatures of 0 °C below the sea ice [69].…”
Section: Response Strategies To Okadaic Acid In Marine Invertebratesmentioning
confidence: 99%
“…No reports have identified the biosynthetic pathway of any secondary metabolite of dinoflagellate origin at the genomic level (Snyder et al, 2005). Although immunological evidence suggests that bacteria inside the sponge Suberites dumuncula as well as sponge cells and intracellular vacuoles all contain OA (Wiens et al, 2003;Schröder et al, 2006), no bacteria that produce a polyketide toxin have been isolated from a dinoflagellate (Wiens et al, 2003;Snyder et al, 2005).…”
Section: Okadaic Acidmentioning
confidence: 99%
“…At elevated concentrations (Ͼ500 nmol l -1 ), OA acts as an apoptogen and promotes expression of the proapoptotic caspase gene with a simultaneous down-regulation of the expression of the anti-apoptotic Bcl-2 homolog gene. In subsequent studies of S. domuncula, Schröder et al (2006) suggested that OA may serve as a defense molecule by inducing apoptosis in symbiotic or parasitic annelids. In other work, Müller et al (2007) demonstrated that OA is required for the expression of the heat shock protein hsp70 at low temperature and contributes to cold tolerance in the sponge Lubomirskia baicalensis.…”
Section: Okadaic Acidmentioning
confidence: 99%
“…Although several studies have successfully used visualization techniques to localize natural products in situ in various marine invertebrates (Gillor et al, 2000;Salomon et al, 2001;Schroder et al, 2006), the methods used in those studies are not feasible for use in bryostatin localization. In order to detect bryostatins in situ, we developed a method based on their clinical molecular target, mammalian protein kinase C (PKC).…”
Section: Introductionmentioning
confidence: 99%